Programa Jugando con los sonidos y niveles de la conciencia fonológica en niños de cinco años de una institución educativa - Caman Nazario, Luz Marina (2010)
The following investigation has the purpose to evaluate the effects of the application of the program “Playing with sounds” in the level of phonologic conscience in a group of Kindergarten children of 5 years old. We utilized a pre experimental design with a non probabilistic sample of 24 students formed by 15 girls and 9 boys of low economic condition from Callao district. Used the metalinguistic skill test: THM to evaluate the results that we obtained. It was adapted to our context by Noemí Panca before and after applying the program that lasted three months. The results show us a significant performance (after the application of the program) that is bigger than others in all the levels of phonologic conscience. The level rhyme got the higher significant performance while phoneme level got the lower one. We conclude that “Playing with sounds” program has positive effects upon the phonologic conscience of kindergarten children.